2022
DOI: 10.3390/su141912169
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Aid for Trade on Human Development in South Asia

Abstract: Although South Asia has made some progress in human development over the last century, it still lags behind some other Asian countries. It is necessary to explore the factors that contribute to human development but have not yet been explored. Thus, the aim of this study is to explore the influence of aid for trade on human development in South Asia for the period 2005 to 2019. First, the study detected the unit root problem in the data using panel unit root tests and found that all data series (human developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…From their analysis of countries in South and East Asia, Africa, and the Paci c, Ashena and Dong (2022) concluded that reducing tariffs stimulates agricultural production, which in turn raises unskilled workers' incomes. Finally, focusing on six South Asian countries (Bangladesh, Bhutan, India, Nepal, Pakistan, and Sri Lanka), Sardar et al (2022) found that AfT has improved human development.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…From their analysis of countries in South and East Asia, Africa, and the Paci c, Ashena and Dong (2022) concluded that reducing tariffs stimulates agricultural production, which in turn raises unskilled workers' incomes. Finally, focusing on six South Asian countries (Bangladesh, Bhutan, India, Nepal, Pakistan, and Sri Lanka), Sardar et al (2022) found that AfT has improved human development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, donor countries began requiring aid-receiving countries to reduce import restrictions and liberalize their trade policies. Meanwhile, to maximize the bene ts of foreign trade for these countries, donors introduced aid for trade (AfT) initiatives, which combined foreign aid and trade strategies with the aim of raising living standards (Sardar et al, 2022; Van Der Sluis and Durowah, 2018; Lee and Oh, 2022). As Gnangnon (2020b) puts it, AfT refers to foreign aid that aims to expand developing countries' participation in international trade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we performed a panel autoregressive distributed lag model (ARDL) approach to assess both the long-and short-run relationship that exists between the variables. The panel ARDL model is widely used by authors to investigate long-run co-integration (see Sardar et al, 2022;Radmehr et al, 2022;Karangwa & Su, 2023). Next, we utilized Fully Modified Ordinary Least Square (FMOLS) and Dynamic Ordinary Least Square (DOLS) models to capture the co-integration between the indicators of accountable government and economic growth.…”
Section: Data Sources and Variablesmentioning
confidence: 99%
“…There is a mutual reinforcement between industrial agglomeration and exports. In recent years, numerous studies have explored the various factors affecting trade exports [8] and the effects of trade on human activities [9][10][11]. Since China's reform and opening up, foreign trade has developed rapidly, greatly contributing to its economic and social development.…”
Section: Industrial Agglomeration and Exportsmentioning
confidence: 99%